Prosecution of grave violations of human rights in light of challenges of national courts and the International Criminal Court: the Congolese dilemma - Didier, Boukongou Jean (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2004.